2006
DOI: 10.1095/biolreprod.105.046029
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Amniotic Fluid-Derived Stem Cells Express Characteristics of Both Mesenchymal and Neural Stem Cells1

Abstract: Recent evidence has shown that amniotic fluid may be a novel source of fetal stem cells for therapeutic transplantation. We previously developed a two-stage culture protocol to isolate a population of amniotic fluid-derived mesenchymal stem cells (AFMSCs) from second-trimester amniocentesis. AFMSCs maintain the capacity to differentiate into multiple mesenchymal lineages and neuron-like cells. It is unclear whether amniotic fluid contains heterogeneous populations of stem cells or a subpopulation of primitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
182
2
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(203 citation statements)
references
References 42 publications
10
182
2
8
Order By: Relevance
“…In recent years, several studies have demonstrated the ability to isolate amniotic membrane stem cells (AMSCs) and amniotic fluid stem cells (AFSCs) (In 't Anker et al 2003;Tsai et al 2004;Tsai et al 2006). These cells have phenotypes attributable to pluripotent cells and can differentiate into different cell types due to the three different embryonic layers (De Coppi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the ability to isolate amniotic membrane stem cells (AMSCs) and amniotic fluid stem cells (AFSCs) (In 't Anker et al 2003;Tsai et al 2004;Tsai et al 2006). These cells have phenotypes attributable to pluripotent cells and can differentiate into different cell types due to the three different embryonic layers (De Coppi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be seen whether these alternatives would lead to any advantage, or disadvantage, in clinical-grade processing. Also, it remains to be determined whether amniotic stem cells recently obtained by somewhat different methods and described as more primitive than purely mesenchymal are actually the same cells that we and others refer to as AMSCs, which have been shown to be able to give rise to cells from more than one germ layer [13,14].…”
Section: Discussionmentioning
confidence: 92%
“…Our AFNSCs maintained or increased their expression of these markers during long-term cultivation in vitro. AF has been identified as an ideal source to isolate fetal multipotent stem cells (AFSCs) [24,39]. AFSCs also express some markers with mesenchymal stem cells, such as CD73, CD105, and CD117, and some pluripotent stem cell markers, such as Oct-4, Nanog, and Sox2.…”
Section: Figmentioning
confidence: 99%